Mutual Learning Between Students and Community in Solving Community-Based Tourism Actors' Problems: Proses Saling Belajar antara Mahasiswa dan Komunitas dalam Menyelesaikan Masalah Pelaku Pariwisata Berbasis Komunitas - Purnomo, Agustina Multi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
The Nusantara Module program at Djuanda University focused on student learning and practice within the local community context. Community service activities were conducted to build a social learning process for students. The activities employed a participatory social learning method to facilitate mutual learning between students and the local community. The contextual study identified community-based tourism as the learning focus in the Bogor regency's context and the Saung Lebah Madu Paseban community as the learning partner. The activities were carried out over two weeks, including planning, implementation, and evaluation based on the partner's needs. Partner selection was conducted in collaboration with the Regional Tourism Promotion Agency. Problem identification revealed that the community needed promotion and partnerships with tourism businesses. The activity outcomes included one leaflet, 17 promotional videos, and five article publications. Partnerships with tourism businesses reached an initial agreement stage. However, follow-up cooperation was not brought out due to time constraints. Process evaluation found that the participatory social learning approach effectively facilitated mutual learning between students and partners. The challenges were unequal knowledge and experience among participants. The outcome evaluation revealed that the promotional products satisfied the partner. However, the impact of the promotion could not be measured due to the limited activity duration. In conclusion, the participatory social learning approach fostered mutual learning, particularly for students. Partners learned facilitation and mutual learning processes to meet their needs. The participatory learning approach effectively facilitated community service activities to further community-based tourism development. The activity recommended that facilitators bridge the knowledge and experience gaps between students and partners. A more extended activity duration was suggested to better establish the mutual learning process and evaluate outcomes.